Exploration of Tree Species in Muaro Jambi Temple Complex: EKSPLORASI JENIS POHON DI KOMPLEKS CANDI MUARO JAMBI - Tamin, Rike Puspitasari; Puri, Suci Ratna; Hardiyanti, Rizky Ayu (Media Konservasi, 2019)
Muaro Jambi Temple Complex is one of the mainstays of Jambi Province's tourism which began to be introduced both at domestic and international market. The existence of forest tree species found in the Muaro Jambi temple complex is very important to be maintained. Botany exploration activities in the Muaro Jambi temple complex are very important to carry out in order to invent and identify the existing tree species. The data obtained will be useful in the conservation and preservation of tropical forest plants activities comprehensively. This research was carried out at Kotomahligai Temple in the water catchment area / along the river of Muaro Jambi Temple Complex, Muara Jambi Village, Muaro Sebo District, Muaro Jambi Regency also  Silviklutur Laboratory and Herbarium of the Faculty of Forestry, Jambi University. The study was conducted for six months from April to October 2018. The purpose of this study was to determine the types of trees found in the Mahligai Temple area and water catchment area of ​​the Muaro Jambi Temple Complex. This study uses a purposive sampling method. The research activities consist of exploration, herbarium specimens, literature studies, species identification. The results showed there were 17 families, including: Anacardiaceae, Burseraceae, Cucurbitaceae, Dilleniaceae, Euphorbiaceae, Fabaceae, Hyperaceae, Lythraceae, Malvaceae, Meliaceae, Moraceae, Oxalidaceae, Phyllanthaceae, Rubiaceae, Salicaceae, Sapindaceae, Verbenaceae. The most abundant species were Peronema canescens Jack (Sungkai) (86 individual trees) and Lansium parasiticum (Duku) (38 indivisual trees). Keywords: exploration, Muaro Jambi Temple, tree species